Respuesta :

8. Answer:  (C) 101.3

Step-by-step explanation:

Use the Law of Cosines:

c² = a² + b² - 2ab·cos C

28.2² = 16.9² + 19.5² - 2(16.9)(19.5)·cos C

795.24 = 285.61 + 380.25 - 659.1 cos C

795.24 = 665.76 - 659.1 cos C

129.38 = - 659.1 cos C

-0.196 = cos C

cos⁻¹ (-0.196) = cos⁻¹ (cos C)

101.3 = C

**********************************************************

10. Answer:  (A) 27.9

Step-by-step explanation:

Use the Law of Cosines:

c² = a² + b² - 2ab·cos C

c² = 25² + 18² - 2(25)(18)·cos 79

c² = 625 + 324 - 900 cos 79

c² = 949 - 171.7

c² = 777.3

√c² = √777.3

c = 27.9